Capacity Building of Society Affected By Floods Through Local Volunteer Community In Dringu Village Probolinggo City - Wahyuni, Hayu; Suhartini, Elly; Arifiyanti, Jati (University of Jember, 2022)
Dringu Village is a village that floods often occur that is every rainy season. In 2021 Dringu Village experienced a servere flash flood disaster that had many impacts on the Dringu Village community. After the flood disaster, the people of Dringu Village formed a “komunitas relawan lokal” to be able to help each other. This local volunteer community was formed by the concerned of the community affected by the flood disaster. Those who join the “komunitas relawan lokal” are people affected by the flash flood disaster and the community of women. Community participation in disaster management can create a development of community capacity in facing flood disasters. This research uses a qualitative method, analyzed uses theory of communicative action by Jurgen Habermas. Keywords: dringu village; komunitas relawan lokal; flood; capacity